2015
DOI: 10.21100/msor.v14i1.253
|View full text |Cite
|
Sign up to set email alerts
|

Maths Arcade at Sheffield Hallam University: Developments made in a new space

Abstract: The Maths Arcade at Sheffield Hallam University has been developed since it was established in 2012. The move to a new space has led to an increase in its popularity and inter-year interactions. It has added to the extensive number of factors that help ease the transition into university. In particular, it now features in the induction week programme and plays a part in our peer assisted learning scheme. In addition to the weekly sessions enjoyed by the students, the Maths Arcade has also been used at a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…This has had some success, including indications that students feel like part of a "mathematics community" (p. 600). Students are positive about the integration of the Maths Arcade into this new space, with positive feedback and increased popularity of the activity reported by Cornock (2015).…”
Section: The Maths Arcadementioning
confidence: 99%
“…This has had some success, including indications that students feel like part of a "mathematics community" (p. 600). Students are positive about the integration of the Maths Arcade into this new space, with positive feedback and increased popularity of the activity reported by Cornock (2015).…”
Section: The Maths Arcadementioning
confidence: 99%
“…Gaps are built in the timetable to ensure that students have the opportunity to take part. As presented by Cornock (2015), "the Maths Arcade is enjoyed by students in all the year groups". Also presented in the paper, the evaluation in 2014-15 showed that it helped students to make friends, they got to know staff better, and inter-year interactions increased.…”
Section: Maths Arcadementioning
confidence: 99%
“…During the lecture, the PAL scheme is introduced and students meet their PAL group. In the rest of the week, the students take part in a quiz, meet their PAL leaders at the Maths Arcade as presented in Cornock (2015), meet their academic supervisor, take part in a team building event, and carry out other activities.…”
Section: Induction Week Programmementioning
confidence: 99%
See 2 more Smart Citations